Sistem Manajemen Organisasional Perusahaan Kerajinan Kulit dalam Memenuhi Kebutuhan Pasar - Tugimin Tugimin (Jurnal Maksipreneur, 2015)
Organizational management system combines all management functions within an organization's productive holistically built based on the concept of quality, teamwork, productivity and customer satisfaction. Be as creative industries leather craft is required to follow the changes and able to meet the needs of the market. Change the orientation of the market take effect directly against the durability of micro, small and medium-sized leather craft, it takes a flexible company management system in maintaining continuity of effort, that it took creativity and innovation on an ongoing basis. Among the many leather companies in Yogyakarta were selected for this study are "CV D & D Leather Handycraft". Through kuantitatif research method system of organizing the company confirms that the craft's skin, between the interelasi policy (team work) in organizational management system is determined by the ability of human resources creative and innovative.